Emergency Ultrasound in the Context of Cardiac Arrest and Circulatory Shock: “How to Avoid Cardiac Arrest” - Rudolf Horn; Michael Blaivas; Daniel Wastl; Guido Michels; Armin Seibel; Susanne Morf; Marco Widler; Christoph F. Dietrich (Life)
In the recently published 2021 European Resuscitation Council Guidelines on Adult Advanced Life Support, focused echocardiography was upgraded to a target recommendation. Several key recommendations were made, including that point-of-care ultrasound (POCUS) should only be used during CPR performed by experienced users and prolonged interruptions longer than 10 s (as accepted for pulse checking) during chest compressions should be avoided. Ultrasound does not replace clinical evaluation nor awareness of the clinical scenario. However, in addition to other assessments such as laboratory analyses, ultrasound can help to directly identify a cause for the peri-arrest state. The advantage of ultrasound is that examinations can be performed at the bedside while other tests are being carried out and repeated as frequently as required. This article focusses on how to use ultrasound during peri-arrest situations, requirements for ultrasound equipment, reversible causes of cardiac arrest, and the use of the RUSH protocol, focused echocardiography, and “deresuscitation” (post resuscitation/return of spontaneous circulation).